Sierra Leone : 2010 Article IV Consultation and First Review Under the Three-Year Arrangement Under the Extended Credit Facility, Request for Modification of Performance Criterion, and Financing Assurances Review-Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Sierra Leone. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
After a period of economic slowdown, the outlook for Sierra Leone appears more favorable. Development priorities and their financing while maintaining a competitive economy and a sustainable debt outlook will help. Structural reforms will focus on improving tax administration, strengthening public financial management, and deepening the financial sector. A key constraint to economic growth in the medium term is the lack of basic infrastructure. Executive Directors support the request to modify the target on net domestic bank credit to the government.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet